2018
DOI: 10.1159/000490693
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stress and Glial Differentiation Effects of a Novel Combination of Cucurbitacin B and Withanone (CucWi-N): Experimental Evidence

Abstract: Background: Natural extracts and compounds used in traditional home medicine are known for their safety and a variety of health promoting and therapeutic potentials. In contrast to the single molecule mediated targets, the combinational therapies are preferred for their multi-functional and limited toxic regimens and may be useful for disease therapeutics as well as to increase the quality of life during a variety of environmental stresses. Purpose: We aimed to combine the active ingredients of Chinese (Helict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that there is no obvious toxicity to normal cells at CuB concentrations lower than 5-10 μM [16]. Wakimoto et al showed that when nude mice transplanted with MD-MB-231 tumor cells were injected with CuB (1 mg/kg) intraperitoneally for 6 weeks, the tumor volume reduced by 55% compared to the control group while body weight did not reduce [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is no obvious toxicity to normal cells at CuB concentrations lower than 5-10 μM [16]. Wakimoto et al showed that when nude mice transplanted with MD-MB-231 tumor cells were injected with CuB (1 mg/kg) intraperitoneally for 6 weeks, the tumor volume reduced by 55% compared to the control group while body weight did not reduce [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the brain functions deteriorate with prolonged exposure to a variety of stresses [12]. Brain-derived cells in culture have been established as a reliable model to study the molecular mechanism of stress-induced damage and its prevention/recovery by natural and synthetic reagents [5,15,39]. In these premises, we used C6 cells in conjunction with a variety of stress models including oxidative stress, smoke, hypoxia, heat-stress, metal and emotional stress to investigate the anti-stress potential of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules have been suggested for this purpose. We previously showed the potential of natural compounds like the marine carotenoids and cucurbitacin B-withanone cocktail to induce astrocytic morphology and mixed type biochemical differentiation in rat glioma cells [5,15]. Proteins with the most remarkable changes included GFAP (indicating astrocytic differentiation) and MAP2 (indicating neuronal differentiation).…”
Section: Discussionmentioning
confidence: 99%
“…In modern scientific approaches, it exerted neuroprotection against Alzheimer's disease models and anti-inflammatory effects in brain cells [21,22]. In combination with cucurbitacin B, WN protected from oxidative stress by lowering antioxidants [23]. Hence, WN may be a powerful substance whose antidepressant and stress-reducing effects should be further investigated.…”
Section: Introductionmentioning
confidence: 99%